Pengaruh Akuntabilitas dan Transparansi Terhadap Minat Muzakki Membayar Zakat di BAZNAS Sragen - Nur Kabib; Ahmad Ulil Albab Al Umar; Ana Fitriani; Lora Lorenza; Muammar Taufiqi Lutfi Mustofa (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to analyze the effect of accountability and transparency on muzakki's interest in paying zakat. The population in this study are people who pay zakat in BAZNAS, Sragen Regency. The sample in this study produced 100 respondents. The sample selection technique used purposive sampling and then used the Slovin formula. The data analysis method in this study uses multiple linear regression. The results of this study indicate that partially the accountability variable that affects the interest in paying zakat, then partially the transparency variable does not have a significant effect on the interest of muzakki to pay zakat. Simultaneously, the variables of accountability and transparency have an effect on the interest in paying zakat.